Dosierung und Toxizität von Antirheumatika bei Niereninsuffizienz = Dosage and toxicity of antirheumatic drugs in renal insufficiency - Weiner, Stefan; Bergner, Raoul (Zeitschrift für Rheumatologie, 2015)
Background: Patients with inflammatory rheumatic diseases frequently have a reduced renal function. The risk of adverse events is increased in these patients and treatment options in patients with rheumatic disease and renal failure are poorly studied. Methods: A selective literature search was carried out for pharmocokinetics, dosage and toxicity of antirheumatic drugs in patients with renal insufficiency. Results: The use of nonsteroidal anti-inflammatory drugs (NSAID), cyclooxygenase(COX)-2 inhibitors, gold and cyclosporine is limited in renal insufficiency due to nephrotoxicity. Methotrexate should not be used in patients with a glomerular filtration rate (eGFR) < 45 ml/min, because of the unpredictable pharmacokinetics with a risk for fatal pancytopenia. The dosage of sulfasalazine, azathioprine, mycophenolate mofetil, cyclophosphamide and antimalarial drugs should be reduced in patients with moderate and severe renal insufficiency. In contrast, leflunomide and numerous biologics can be used without dosage modification; however, biologics with a molecular weight < 60 kDa (e.g. anakinra) are an exception and should be reduced in patients with renal insufficiency. Overall, there are only limited data on the use of biologics in this population. Numerous comorbidities and the high risk for infection should be kept in mind when patients with rheumatic disease and renal failure are treated with immunosuppressive drugs. Conclusion: Further studies are necessary to obtain more evidence on the use of disease-modifying antirheumatic drugs (DMARD) and biologics in patients with renal insufficiency.